Potensi Tanaman Endemik Sulawesi Tengah Etlingera Tjiasmantoi Sebagai Kandidat Obat Antituberkulosis Baru: Studi In Silico Dan In Vitro - Azzahra, Zahwa; Amalia , Nurul Izza; Nursagita, Zhafirah Tri; Febriyadi, Febriyadi; Wardhani, Shara; Ihwan, Ihwan; Jamaluddin, Jamaluddin (Universitas Borneo Lestari, 2025)
Plants of the Zingiberaceae family have a lot of potential as medicinal raw materials, especially the Etlingera genus which has antimicrobial activity. It is suspected that secondary metabolite compounds in the Etlingera genus play an important role in antimicrobial activity by activating STAT that affects the production of cytokines and chemokines that are important in fighting Mycobacterium tuberculosis bacteria, as is the case with the newly discovered Etlingera tjiasmantoi species as an endemic plant that is empirically used as an anticancer. This research was conducted to determine the potential of ethanol extract of Etlingera tjiasmantoi leaves as an antituberculosis in silico and in vitro. The research method went through two stages, namely in silico with the stages of network pharmacology test, molecular docking, and prediction of Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) of compounds and in vitro to validate the results of in silico testing using the Resazurin Microtiter Assay (REMA) method. The results of in silico analysis showed that the Etlingera tjiasmantoi plant has a 2-Methyldecalin compound with a binding energy of -6.2 which is smaller than the isoniazid control ligand so that it has a strong bond with the JAK2 target protein and a good ADMET profile orally, in vitro tests showed that concentrations of 500 ppm and 750 ppm were able to fight Mycobacterium tuberculosis bacteria so that the ethanol extract of Etlingera tjiasmantoi leaves has the potential as a new antituberculosis drug candidate.